Bending behaviour of timber beams strenghthened using bonded-in plates / Hafizah Muhamad Azlan - Muhamad Azlan, Hafizah (2013)
The structural of timber is usually limited by the relatively low bending stiffness and strength of the material in relation to other product like concrete and steel. Solid timber beam with bigger size are difficult to b obtained. Therefore, the timber beams at factory or existing timber beams that have been built can be strengthened and give equivalent load carrying capacity similar to beam with bigger size. One potential solution to increase the stiffness and strength of the timber is by reinforcing them with plates or rod . In order to attach the reinforcement to timber the use of structural adhesive has been widely accepted ' with condition that the bond formed should be strong enough to transfer shear from one substrate to another. Adhesive can be used to form load-bearing joint in timber structure , both in repair and in new-build applications. An adhesive is expected to hold material together and transfer design loads from one adherend to other within a given service environment for the life of the structure.